PENGARUH ASPEK SOSIAL BUDAYA PADA DESAIN INTERIOR HOTEL NIAGARA DI LAWANG - Paul, Ferry Sanjaya (Dimensi Interior, 2008)
The Influence of culture and social aspects in the interior design of Niagara hotel in Lawang is a research taking the time perspective of the Colonial phase (1900-1942), the phase when Niagara hotel began to be build. During that phase, there was a social penal system that triggered competitions among the people to receive appreciation or recognition of social honor among the middle class (the Chinese) society. The form of competitive interactions in the Chinese community is to get appreciation or honorable recognition by revealing their life aspects to the high class community, the Europeans. As a case study in this subject matter, Liem Sian Yu, a part of the middle class society, built the Niagara Hotel. All his competitive experiences to achieve appreciation or social recognition from the society during that time were actualized through the style, the choosing and processing of materials, and the balanced design principles applied in the Niagara Hotel. Abstract in Bahasa Indonesia: Penelitian ini mengambil perspektif kurun waktu fase kolonial (1900-1942) yaitu fase dimana bangunan Hotel Niagara mulai didirikan. Pada fase ini terdapat sistem pelapisan sosial yang melahirkan adanya persaingan antar individu untuk mendapatkan sebuah penghargaan atau pengakuan kehormatan sosial dikalangan masyarakat lapisan tengah (Cina). Bentuk interaksi persaingan dalam masyarakat Cina dihadapi dengan mengacukan aspek kehidupannya pada golongan masyarakat lapisan atas yaitu Eropa. Demikian pula Liem Sian Yu yang merupakan bagian dari masyarakat lapisan tengah (Cina) sebagai subyek dalam perancangan Hotel Niagara. Apa yang dialaminya dalam bersaing untuk mendapatkan sebuah penghargaan atau pengakuan kehormatan sosial dari masyarakat di sekitarnya pada masa itu diwujudkan melalui pengacuan gaya, pemilihan dan pengolahan bahan, serta pemakaian prinsip desain keseimbangan pada interior Hotel Niagara. Kata kunci: Sosial budaya, interior, hotel niagara.